Common complaints in couple therapy : new approaches to treating marital conflict - Lachkar, Joan (New York : Routledge, Taylor & Francis Group, 2014)
'Marriage and couple therapists see clients with broken relationships and bonds all the time; those who were once madly in love can grow indifferent, people change, and couples go into sessions feeling depressed, traumatized, and sometimes abused by their partners. Joan Lachkar examines the vicissitudes of love relations by taking into account aspects of aggression, cruelty, sadism, envy, and other primitive defenses lurking in the shadows of love and intimacy. Each chapter revolves around a specific situational conflict, with guidelines and treatment suggestions offered to the therapist. Numerous vignettes and detailed descriptions of theoretical technique, methodology, and diagnostic distinctions are included throughout the book to help readers see theory in action. The theoretical concepts drawn on include psychoanalysis, object relations, self-psychology, attachment theory, DBT, mindfulness, and others, with a heavy emphasis on listening and non-verbal and verbal communication throughout'--
Includes bibliographical references (pages 175-179) and index.
Keywords: Couples Therapy; Marital psychotherapy